Analysis of Similarities Between Five Indigenous Bio-Catalyst Extracts used by Several Communities in Kenya - Chaka, Bakari; Aloys, Osano; Martin, Magu (European Scientific Journal, ESJ, 2020)
Commercial fermentation additives are quite expensive leading to increased production costs. Several communities in Kenya have continuously enjoyed fast saccharification of biomass during cooking and fermentation of porridge and ethanol using bio-catalysts. Infusion of these bio-catalysts into modern-day science is crucial in optimization of yields and reduction of production costs in food, alcohol, pharmaceuticals and energy industries. This study aimed at characterizing five extracts (Terminalia b., Acanthaceae spp., Osyris lanceolata, Santaraseae spp. and Kigelia africana) for possible similarities in physical-chemical parameters, elemental composition and ionic stability. Water extracts were preferred as natively done by these communities. Wet chemistry was used for physical-chemistry parameters and elemental composition while spectroscopy was used to analyze presence of bio-metals, functional groups, conjugation and ligands present. Lab simulation studies were conducted to evaluate ionic stabilities. The results indicated the samples had similar pH, conductivity and volatile solids with slight variations in alkalinity and fatty acids. There were similarities in the functional group peaks and conjugation patterns. The ions of Cu(OH)2, Fe(OH) 2+ , ZnOH+ , Cr(OH) 2+ and Co 2+ were found to be dominant in all biocatalyst extracts. Terminalia b. and Osyris lanceolata were found to have relatively higher sulfate, phosphate levels while nitrate levels were similar in all the samples except for Terminalia b. biocatalysts. These compounds extracted from these herbs can be commercialized for industrial fermentation processes.